Environmental factors that distinguish between clinical and healthy samples with childhood experiences of abuse and neglect - Infurna, Maria Rita; Parzer, Peter; Kaess, Michael (Psychopathology, 2015)
Childhood maltreatment is associated with a wide range of problems in adulthood. However, specific environmental factors (either positive or negative) influence mental health outcomes in maltreated children. The present study investigated the effect of environmental factors by comparing a group of clinical participants with experiences of abuse/neglect with a healthy group with similar patterns of experiences. Environmental factors selected were: separation from parents, financial hardship, parental psychiatric disorders, and low social involvement. Method: The study included 55 mixed clinical participants and 23 healthy participants. All participants were investigated using the Childhood Experience of Care and Abuse (CECA) interview. The two groups were specifically matched with regard to patterns of childhood maltreatment. Results: The findings indicated that psychopathological outcome was associated with a greater presence of negative environmental factors (p < 0.001). In particular, lack of social support seemed to be the only one predictor (OR = 27.86). Conclusion: This study is the first to investigate the influence of specific environmental factors in two groups with similar childhood experiences of abuse/neglect but different mental health outcomes. These findings suggest that efforts should be made to incorporate both familial and external sources of social support in promoting mental health for maltreated children.
Gesehen am 05.06.2020